USE OF MEDICINAL PLANTS BY THE VILLAGERS OF TAPOTZINGO, NACAJUCA, TABASCO, MEXICO. - Alejandro, Miguel Alberto Magaña; Mendoza, Manuel Sanchez; Rodríguez, Merly Iveth Magaña (European Scientific Journal, ESJ, 2014)
Health services are one of the most pressing needs in the communities of Mexico and Tabasco, this is because in various rural regions do not have affordable health care or economic resources to access this service in particular. These problems occur primarily the indigenous groups Chontals of Tabasco.From 2009 to 2011, we conducted an ethnobotanical research in five villages in the municipality of Nacajucaamong which the village of Tapotzingo, where is concentrated the greater presence of indigenous groups, Tabasco Chontal.